2004
DOI: 10.1159/000076531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Puberty on the Relationship between Bone Markers of Turnover and Bone Mineral Density in Turner’s Syndrome

Abstract: It has been suggested that the appropriate timing of puberty is necessary for normal bone mineral acquisition which may not be achieved amongst patients with Turner’s syndrome (TS). The aim of this study was to assess bone mineral density (BMD) and bone turnover in 34 patients with TS (age range 2.2–39.0 years). The areal BMD (aBMD) was determined by dual-energy X-ray absorptiometry, and the volumetric BMD was calculated. Blood and second voided urine samples were taken the morning after an overnight fast for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The relationship between biochemical bone markers, bone density, and endocrine changes of puberty in normal girls are thus not completely understood, and studies in TS are sparse. One study found increased levels of bone formation and resorption mainly in prepubertal girls with TS but no control group was included [17]. With the age distribution in our cohort, we anticipated bone cells to be engaged primarily in modeling processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between biochemical bone markers, bone density, and endocrine changes of puberty in normal girls are thus not completely understood, and studies in TS are sparse. One study found increased levels of bone formation and resorption mainly in prepubertal girls with TS but no control group was included [17]. With the age distribution in our cohort, we anticipated bone cells to be engaged primarily in modeling processes.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of aBMD and biochemical bone markers is helpful in fracture risk assessment in postmenopausal women [15]. However, little is known about the relation of aBMD and also vBMD to bone markers in young TS [1,16,17] as well as to sex hormones and other growth factors [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, prepubertal estradiol secretion may also play a role in bone mass acquisition during this period. Adolescents girls with TS and spontaneous puberty have bone mineral density (BMD) in the normal range, while in TS girls who underwent induced puberty (48) and young TS patients do not attain peak BMD despite proper HRT and growth hormone therapy (49).…”
Section: Bone Mass Gain and Prevention Of Fractures In Turner Syndromementioning
confidence: 99%
“…Bone deficiency is most marked at the femoral neck and seems correlated with serum testosterone and estradiol levels (58).…”
Section: Bone Mass Gain and Prevention Of Fractures In Turner Syndromementioning
confidence: 99%
“…24 Sex hormone replacement should be synchronized with GH therapy with continued monitoring for side effects from this therapy as well. 9,34 Conjugated estrogens like Premarin or ethinyl estradiol are the most common form of replacement therapy, while standard lowdose birth control pills are used less often for monthly maintenance. Depending on one's initial height, the desire for reproduction, concerns for osteopenia, osteoporosis or atherosclerosis, GH therapy schedules, and personal preferences, sex hormone replacement regimens, doses, and length of therapy should be determined on an individual basis.…”
Section: Endocrine the Pituitary-ovarian Axismentioning
confidence: 99%